Adaptações sensório-motoras em curto prazo após uma única sessão de terapia robótica associada ao videogame - Couto, Marcela de Abreu Silva (2017)
Robotic device deployment used for the recovery of people with hemiparesis is increasing. This resource can be associated to video games and different levels of assistance can be used for specific and oriented tasks. However, there are insufficient guidelines to prescribe rehabilitation therapy of the lower limbs. The first aim of study was to verify whether a single session of robotic therapy promotes short-term ankle motor adaptations, influencing the coordinate movements (sub-maximum torque maintenance of ankle – steadiness), maximal strength outcomes, such as torque, power and work and functional performance in chronic post-stroke individuals; and the second objective was to describe the analysis the metric data related to accuracy, speed, smoothness and movement initiated without assistance, as well as trajectory variation recorded during robotic ankle therapy protocol based on the criteria of increasing and decreasing impedance adjustments. Both studies had double-arm pilot design, on a convenience sample of participants with chronic stroke (n = 14) who had residual hemiparetic deficits and an equal number of age- and sex-matched non-disabled control subjects. In the first manuscript, balance, mobility and function were measured. Concentric isokinetic and steadiness tests were assessed using dynamometry. The maximum and minimum muscle activation peaks were recorded by electromyography simultaneously with concentric tests. For submaximal sensorimotor control analysis (Steadiness), the standard deviation, coefficient of variation and root mean standard error (RMSE) were recorded. In the second manuscript, game score, movement initiated without assistance, initiation time, mean speed, number of speed peaks and trajectory variation were variables recorded over seven blocks with variable assistance levels. A motivation questionnaire was given to the hemiparesis group. The main results were motor adaptations in sub maximum maintenance, which were identified preferentially during the dorsiflexion. The hemiparesis group showed greater dexterity, initial reaction and smoothness during dorsiflexion post-robotic assistance therapy. People with chronic hemiparesis presented short-term performance gains in submaximal torque maintenance, especially during dorsiflexion after a single robotic therapy session. The actual robotic therapy protocol promoted preservation and maintenance of neuromuscular performance when compared to the healthy control group. In addition, analyzing the metric data obtained during the robotic therapy session corroborated to identify motor adaptation related to the speed, accuracy and errors in the trajectory position. Moreover, impedance change strategy was effective to promote challenge and motor control adaptation.